Pathogenesis and treatment of wound healing in patients with diabetes after tooth extraction - Yang, Shuting; Li, You; Liu, Chengcheng; Wu, Yafei; Wan, Zixin; Shen, Daonan (Frontiers in Endocrinology, 2022)
Diabetes mellitus is a common systematic chronic disease amongst dental patients. The elevated glucose microenvironment can prolong the healing of tooth extraction sockets. Therefore, the promotion of healing up tooth extraction sockets is of great clinical importance to patients with diabetes mellitus. The current evidence indicates the mechanism of the recovery period of extraction sockets in hyperglycemia conditions from physiological, inflammation, immune, endocrine, and neural aspects. New advancements have been made in varied curative approaches and drugs in the management of wound healing of tooth extraction sockets in diabetes. However, most of the interventions are still in the stage of animal experiments, and whether they can be put into clinical application still needs further exploration. Specifically, our work showed topical administration of plasma-rich growth factor, advanced platelet-rich fibrin, leukocyte- and platelet-rich fibrin, bisphosphonate, and hyaluronic acid as well as the maxillary immediate complete denture is regarded as a promising approach for clinical management of diabetic patients requiring extractions. Overall, recent studies present a blueprint for new advances in novel and effective approaches for this worldwide health ailment and tooth extraction sockets healing.